The Use Of Scrubble Game To Improve Students Vocabulary Mastery. - Sahabir, Gloria; olii, Sanerita T.; Rorimpandey, Rinny S (Program Studi Pendidikan Bahasa Inggris, 2025)
The purpose of this research was to find outwhether or not scrabble game can be used to improve student’s vocabulary mastery. In terms of purpose, this research was a quantitative research. In this research, the researcher asked students’ opinions about the use of scrabble game to improve the vocabulary mastery. In terms of the nature of data, since the data collected using questionnaire were put into frequency distribution, this survey was categorized as a quantitative research. The data obtained in this study reveals that (1) 94% of the students strongly agree and agree that scrabble game is interesting and effective technique that can be used to improve and motivate the respondents to engage in vocabulary; (2) 79% of students strongly agree and agree that being engaged that scrabble game is interesting and effective technique that can be used to improve and motivate the respondents to engage in vocabulary follow all group discussion activities; (3) 92% of the students strongly agree and agree that their engagement that scrabble game is interesting and effective technique that can be used to improve and motivate the respondents to engage in vocabulary in English; and (4) 87% of the students (respondents) enjoyed being involved in that scrabble game is interesting and effective technique that can be used to improve and motivate the respondents to engage in vocabulary the technique. It can then be concluded that the students positively consider group discussion an interesting, effective and useful technique for it can be used to improve their engagement, motivation skills in English.